The use of icts as a tool for meaningful learning of the English language - Anaya Velasco, Yully; Díaz Rodríguez, Silvia; Martínez Hernández, Jenny (Rastros Rostros, 2012)
This article describes the arduous development of a survey conducted with primary school students at the Escuela Normal Superior de Bucaramanga. This research project “Interaction between icts a nd bilingual teaching as a functional learning alternative”,focuses on the use of icts in the process of teaching and learning English. The methodology used for this research is an educational Blog for the students. The researchwas based on the work of David Ausubel (1983) and his theory of meaning ful learning.
Keywords: meaning ful learning; teaching; english; motivation; ict